Chest X-ray findings in COVID-19 patients: a descriptive study - Hussain, Asraf; Mishra, Jeetendra; Karn, Achutanand Lal; Singh, Alok Kumar; Ansari, Parwez; Akhtar, M. Kalim; Rimal, Bikranta; Shah, Dambar; Mahato, Rajan; Bista, Sagun; Singh, Aadarsh; Kushwaha, Omprakash; et al. (International Journal of Advances in Medicine, 2021)
Background: Early suspicion and diagnosis remains the cornerstone for the better outcome of patients and to decrease cross infection in cases of COVID-19 pneumonia. In a country like Nepal X-ray facilities are readily available radiological tool in most of the centers and can be important screening tool. There is a lack of studies detailing the chest XR (C-XR) findings in these patients when compared to that dedicated to the CT features. Study aims to describe the patterns of the lung opacities in CXR in these patients. Methods: This is retrospective descriptive study conducted at NMCTH in COVID-19 patients from 12 September to 17 October 2020. Demographic characteristics, symptoms, co-morbidities and C-XR findings were studied. CXR findings were categorized according to BSTI classification. Results: Among 111 COVID-19 RT-PCR positive cases admitted 102 (91.9%) belonged to age group 18-65 years, 89 (80.2%) were males. Cough and fever were the commonest symptoms present in 109 (98.2%) patients. Ischemic heart disease and hypertension in 32 (28.8%) patients were the commonest co morbidities. According to British society of thoracic imaging (BSTI) COVID-19 CXR classification, six patients (5.4%) had normal chest X-rays. Classic/probable COVID-19 picture was present in 79 (71.17%) patients while (7.2%) had intermediate for COVID-19 X-ray findings. Among 79 patients with classic/probable COVID-19 CXR findings 71 (89.8%) had bilateral consolidation/ground glass haze, 72 (91.1%) had peripheral lung involvement while 66 (83.5%) had middle and lower zone involvement. Conclusions: Ground glass opacities/consolidations with bilateral location, peripheral distribution and middle- lower zone predominance were the commonest X-ray findings in our study.